Postsplicing-Derived Full-Length Intron Circles in the Protozoan Parasite Entamoeba histolytica - Mendoza-Figueroa, María S.; Alfonso-Maqueira, Eddy E.; Vélez, Cristina; Azuara-Liceaga, Elisa I.; Zárate, Selene; Villegas-Sepúlveda, Nicolás; Saucedo-Cárdenas, Odila; Valdés, Jesús (Frontiers in Cellular and Infection Microbiology, 2018)
Noncoding circular RNAs are widespread in the tree of life. Particularly, intron-containing circular RNAs which apparently upregulate their parental gene expression. Entamoeba histolytica, the causative agent of dysentery and liver abscesses in humans, codes for several noncoding RNAs, including circular ribosomal RNAs, but no intron containing circular RNAs have been described to date. Divergent RT-PCR and diverse molecular approaches, allowed us to detect bona fide full-length intronic circular RNA (flicRNA) molecules. Self-splicing reactions, RNA polymerase II inhibition with Actinomycin D, and second step of splicing-inhibition with boric acid showed that the production of flicRX13 (one of the flicRNAs found in this work, and our test model) depends on mRNA synthesis and pre-mRNA processing instead of self-splicing. To explore the cues and factors involved in flicRX13 biogenesis in vivo, splicing assays were carried out in amoeba transformants where splicing factors and Dbr1 (intron lariat debranching enzyme 1) were silenced or overexpressed, or where Rabx13 wild-type and mutant 5′ss (splice site) and branch site minigene constructs were overexpressed. Whereas SF1 (splicing factor 1) is not involved, the U2 auxiliary splicing factor, Dbr1, and the GU-rich 5′ss are involved in postsplicing flicRX13 biogenesis, probably by Dbr1 stalling, in a similar fashion to the formation of ciRNAs (circular intronic RNAs), but with distinctive 5′-3′ss ligation points. Different from the reported functions of ciRNAs, the 5′ss GU-rich element of flicRX13 possibly interacts with transcription machinery to silence its own gene in cis. Furthermore, introns of E. histolytica virulence-related genes are also processed as flicRNAs.